The NF1 gene mutations and co-mutations in lung adenocarcinomas with brain metastasis - Nesibe Kahraman-Cetin; Dilara Akin; Seda Orenay-Boyacioglu; Olcay Boyacioglu; Ibrahim Halil Erdogdu; Esin Oktay; Ibrahim Meteoglu (Indian Journal of Pathology and Microbiology)
Background: The co-occurrence of lung adenocarcinoma and brain metastasis remains a significant cause of morbidity and mortality despite advancements in cancer treatment. The activity of neurofibromin, the product of Neurofibromatosis Type 1 gene (NF1), is crucial in regulating the RAS/MAPK pathway. The NF1 somatic mutations are significant in conditions such as melanoma, lung cancer, breast cancer, neuroblastoma, and central nervous system tumors. Objective: Therefore, this research aims to uncover the profile of NF1 mutations and co-mutations in patients with brain metastases from lung adenocarcinoma, shedding light on their role in the pathophysiology of metastatic lung cancer. Materials and Methods: In this study, a total of 131 (31 females, 90 males) patients diagnosed with metastatic lung adenocarcinoma who were examined in the Molecular Pathology Laboratory between 2019 and 2022 were retrospectively analyzed. The NF1 somatic mutations and co-mutations were evaluated using the NGS lung panel on the MiniSEQ NGS platform. Results: The average age of the 131 patients (31 females, 90 males) retrospectively examined in the study was 62.05 years. The ages of the cases included in the study followed a normal distribution according to Kolmogorov–Smirnov test (P = 0.200). Lymph node metastasis was detected in 48 patients (36.6%), while distant organ metastasis was observed in 81 patients (61.83%). Metastases were more frequently seen in males. No statistically significant difference was found between metastases and gender (P > 0.05). Distant organ metastasis (n = 26, 19.8%) and NF1 mutations (n = 8/26, 30.77%) were most commonly observed in the brain. The most common NF1 pathogenic variants in brain metastases were c.2325 + 3A > G (p.M1205fs*12) (n = 6/26, 23.07%) and c.1400C > T (p.T4671) (n = 5/26, 19.23%). There was no statistically significant relationship observed between patients’ age, gender, brain metastasis, and NF1 mutation types (respectively, P = 0.98, P = 0.63, and P = 0.87). The mutations that showed the most association with NF1 mutations in brain metastases were PTEN and TP53. Conclusions: Somatic NF1 mutations and co-mutations can play a critical driving force in metastatic lung adenocarcinoma and may contribute to treatment resistance. The mutational landscape of somatic NF1 mutations and co-mutations can provide new insights into the pathophysiology of metastatic lung cancer, especially those that have metastasized to the brain.